Antibiotic Susceptibility among Infective Endocarditis Population: Syndromic Antibiogram Evaluation at Indonesian National Cardiovascular Center - Indrawati, Lilik; Sugianli, Adhi Kristianto; Prakoso, Baskoro Justicia; Gunawan, Adrian; Soerarso, Rarsari; Soesanto, Amiliana M.; Dewi, Andaru Dahesih (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Infective Endocarditis (IE) is a life-threatening disease with a high mortality rate (25%). Laboratory approaches to support the diagnosis of IE especially blood and/or cardiac vegetation culture, are crucial for providing definitive therapy. However, negative culture is frequently observed, therefore empirical use of antibiotics seems unavoidable and may lead to increasing antimicrobial resistance. This study aims to observe the prevalence of antibiotic susceptibility among the IE population using the WISCA approach. This retrospective study observed medical record data of all inpatients diagnosed with IE according to ICD-10 at Cardiovascular Center Harapan Kita Hospital (NCCHK) between January 2018 and December 2022. Patient data were combined with bacterial identification and antibiotic susceptibility test data from the laboratory information system, and evaluated based on period (year). A total of 67,858 inpatients and 1.1% (n=772) were diagnosed with IE. Successful culture growth (blood and/or cardiac vegetation specimen) was between 36.8% and 70% annually. Streptococcus viridans group (82/237, 34.6%) and Coagulase-negative Staphylococci (57/237, 24.1%) were dominantly observed among the IE population. Low susceptibility among Penicillin (34.3%) towards Gram-positive bacteria, as first-line treatment option in IE. Meanwhile, high susceptibility range was observed in Ceftriaxone (95.7%), Gentamicin (80.4%), Rifampicin (84.4%), and Vancomycin (98.7%) as second-line treatment in IE. Despite the low prevalence, the occurrence of antimicrobial resistance in IE has become a priority concern. Continuing the syndromic antibiogram is mandatory to assist the trend of empirical antibiotic usage and refine the established local treatment guidelines.